A confusão esquerda/direita no mundo pós-muro de Berlim: uma análise e uma hipótese - Angelo Segrillo (Universidade do Estado do Rio de Janeiro, 2004)
This article analyzes the modifications undergone by the concepts of "left" and "right" in the world after the fall of the BerlinWall and the disintegration of the USSR. It sheds light on the consequences of these historical and theoretical changes in Brazil and postulates a hypothesis on the role of the left as the prime mover of radical alterations in the dynamic functioning of party systems as a whole.